SOCIO-DEMOGRAPHIC FACTORS' RELATIONSHIP WITH PSYCHOLOGICAL DISTRESS OF UNDERGRADUATE UNIVERSITY STUDENTS OF PAKISTAN - Jillani, Uzma; Malik, Anila Amber (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVETo investigate the relationship of socio-demographic variables (gender, peer group size) with psychological distress in undergraduate university students in Pakistan. STUDY DESIGNCross-sectional studyPLACE AND DURATION OF STUDYThe study was conducted at two public and private universities in Karachi, Pakistan from June to Aug 2022.METHODA total of 300 students aged 19 to 25 years completed a demographic form and the Kessler Psychological Distress Scale (K10).RESULTSFemales reported significantly higher psychological distress than males. Students with three or more friends demonstrated lower distress compared with those reporting no friends.CONCLUSIONGender and peer network size were significant predictors of distress, with males and students having larger peer groups reporting lower psychological distress.